2023
DOI: 10.3390/pharmaceutics15030883
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Linker Amino Acid in the Cell-Penetrating Peptide NickFect55 Leads to Enhanced pDNA Transfection for In Vivo Applications

Abstract: Despite numerous efforts over the last three decades, nucleic acid-based therapeutics still lack delivery platforms in the clinical stage. Cell-penetrating peptides (CPPs) may offer solutions as potential delivery vectors. We have previously shown that designing a “kinked” structure in the peptide backbone resulted in a CPP with efficient in vitro transfection properties. Further optimization of the charge distribution in the C-terminal part of the peptide led to potent in vivo activity with the resultant CPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Another experiment showed that NF55/pDNA complexes with both modified and unmodified linkers could transfect cells in vivo, mostly targeting lung cells. 422 Similar studies of CPP/pDNA complex transfection were conducted for several other CPPs, namely PepFect14, CPP foldamers, DOT1L, Scp01-b, and HR9, but most were conducted in vitro. [423][424][425][426][427] Many studies illustrate another approach, in which CPPs are placed on NP surface to increase cell membrane penetration.…”
Section: Cell-penetrating Peptidesmentioning
confidence: 97%
See 1 more Smart Citation
“…Another experiment showed that NF55/pDNA complexes with both modified and unmodified linkers could transfect cells in vivo, mostly targeting lung cells. 422 Similar studies of CPP/pDNA complex transfection were conducted for several other CPPs, namely PepFect14, CPP foldamers, DOT1L, Scp01-b, and HR9, but most were conducted in vitro. [423][424][425][426][427] Many studies illustrate another approach, in which CPPs are placed on NP surface to increase cell membrane penetration.…”
Section: Cell-penetrating Peptidesmentioning
confidence: 97%
“…CPPs can be used for gene delivery both on their own and as a component of other delivery system. 420 In a recent study, Härk et al 422 used NickFect55 CPP with modified amino acid linker in complex with pDNA to transfect CHO cells, reaching over 60% transfection efficiency. Another experiment showed that NF55/pDNA complexes with both modified and unmodified linkers could transfect cells in vivo, mostly targeting lung cells.…”
Section: Cell-penetrating Peptidesmentioning
confidence: 99%
“…Once the intein undergoes self-excision, the protein and CPP are joined together through a peptide bond. Structures were generated using Mol* [44] software and Marvin [45].…”
Section: Design Of Nanoentity For Intracellular Protein Deliverymentioning
confidence: 99%